TANGGUNG JAWAB NOTARIS TERHADAP PENGAKUAN ANAK DILUAR KAWIN PADA HAK WARIS ANAK PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU/VIII/2010 - Sanusi, Imam; Rato, Dominikus; Ali, Moh. (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2022)
The legal concept regarding the position of a child born out of wedlock who only has a civil relationship with the mother and the mother’s family experienced a shift when the Constitutional Court Decision Number 46/PUU-VIII/2010 was issued. There are 2 (two) issues that will be discussed, namely the rights and status of children illegitimate after the Constitutional Court’s decision, as well as the authority of a Notary in making a Certificate of Inheritance for a Child Out of Wedlock after the Constitutional Court’s Decision. In compiling this research, the writer uses normative research methods which are carried out as an effort to obtain the necessary data in an effort to obtain the necessary data in connection with the problem. From the results of the research it can be obtained that the Constitutional Court’s decision opens opportunities for children outside of marriage to have civil relations with their father and father’s family and the authority of a notary in making certificates of inheritance for children outside of marriage after the decision of the Constitutional Court Number 46/PUU-VIII/2010 becomes very important.